Nutritional approaches to improve the fatty acid profile of milk fat in sheep and goats - Nudda A.; Cannas A.; Pulina G. (Innovation for sustainability in sheep and goats, 2019)
Sheep and goat milk are sources of bioactive compounds with health-promoting properties. The demand for sheep and goat milk has grown worldwide over the years, because of both the increased request for cheese and other traditional dairy products, and the success of sheep and goat milk as component of infant formulas, drinking milk and nutraceutical product. Animal feeding is one of the main factors affecting the quality of fat in sheep and goat milk and, therefore, in the derived dairy products. In particular, nutrition can readily alter milk fat concentration and fatty acid (FA) profile. This review compared the effects of sheep and goats feeding strategies on milk fat composition, with focus on FA with potential healthy properties, such as conjugated linoleic acid (CLA) and polyunsaturated fatty acids (PUFA) of the omega3 family. The nutritional strategies to design the FA profile of sheep and goat dairy products based on grazing and use of vegetable oils and the different nutritional responses of the two species are reviewed and discussed.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)